REPARAÇÃO DE PERFURAÇÃO OCULAR EM CÃO: RELATO DE CASO - da Silva, Tais Lopes; Simão, Iago; Wurfel, Simone de Fátima Rauber; Schneider, Marla; Massa, Isadora Morais; Lusa, Tatiane (Anais de Medicina Veterinária, 2022)
.